Synthesis of Bimetallic Gold-Silver (Au-Ag) Nanoparticles for the Catalytic Reduction of 4-Nitrophenol to 4-Aminophenol - Berahim, Nurafaliana; Basirun, Wan Jefrey; Leo, Bey Fen; Johan, Mohd Rafie (MDPI, 2018)
Bimetallic gold-silver nanoparticles as unique catalysts were prepared using seed colloidal techniques. The catalytic capabilities of the nanoparticles were ascertained in the reduction of 4-nitrophenol to 4-aminophenol in the presence of sodium borohydride. Our results clearly showed that the rate of 4-NP reduction to 4-AP increased with a corresponding decrease in the diameter of the bimetallic NPs. The Au-Ag nanoparticles prepared with 5.0 mL Au seed volume indicated higher reduction activity, which was approximately 1.2 times higher than that of 2.0 mL Au seed volume in the reductive conversion of 4-NP to 4-AP. However, the monometallic NPs showed relatively less catalytic activity in the reductive conversion of 4-NP to 4-AP compared to bimetallic Au-Ag nanoparticles. Our studies also reinforced the improved catalytic properties of the bimetallic Au-Ag nanoparticles structure with a direct impact of the size or diameter and relative composition of the bimetallic catalytic nanoparticles.